The Influence of Profit Persistence, Profitability, Liquidity, and Capital Structure on the Quality of Earnings in Kompas 100 Index Companies 2019-2022 - Putri, Erlyn Nurlita; Pandansari, Tiara; Santoso, Suryo Budi; Santoso, Selamet Eko Budi (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This research aims to empirically test the influence of earnings persistence, profitability, liquidity, and capital structure on earnings quality. This research method uses quantitative data with secondary data sources. The population in this research is the Kompas 100 Index which is listed on the Indonesia Stock Exchange in 2019-2022. The sampling technique used was Purposive Sampling so the data resulted in 54 samples and 26 samples. This research uses multiple linear regression analysis techniques. The results of this research can be state that earnings persistence has a positive effect on earnings quality. This happens because there is investor interest in companies that can maintain their profits. Meanwhile, profitability, liquidity, and capital structure have a negative effect on earnings quality because the level of profitability is low both in the ability to pay short-term debt and the company also uses more capital than paying dividends. So, the company also incurs a lot of costs and the quality of profits decreases. From this, it can motivate management to carry out earnings management.